2004
DOI: 10.1152/ajplung.00194.2003
|View full text |Cite
|
Sign up to set email alerts
|

Arginase inhibition increases nitric oxide production in bovine pulmonary arterial endothelial cells

Abstract: Nitric oxide (NO) is produced by NO synthase (NOS) from L-arginine (L-Arg). Alternatively, L-Arg can be metabolized by arginase to produce L-ornithine and urea. Arginase (AR) exists in two isoforms, ARI and ARII. We hypothesized that inhibiting AR with L-valine (L-Val) would increase NO production in bovine pulmonary arterial endothelial cells (bPAEC). bPAEC were grown to confluence in either regular medium (EGM; control) or EGM with lipopolysaccharide and tumor necrosis factor-alpha (L/T) added. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
186
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(208 citation statements)
references
References 27 publications
22
186
0
Order By: Relevance
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 78%
“…Consistent with this hypothesis, increased vascular arginase activity was reported to contribute to decreased endotheliumdependent NO production in pathologic conditions such as hypertension (19,20), atherosclerosis (21), diabetes (22), and erectile dysfunction (23), or in aging (24). Moreover, even though the regulating factors of arginase expression/activity remain largely unknown, it was demonstrated that various proinflammatory cytokines can act as inducers of arginase expression in cultured endothelial cells (18,25,26).…”
mentioning
confidence: 78%
“…Arginase I expression in macrophages, hepatocytes, and vascular smooth muscle cells, is stimulated by lipopolysaccharide (LPS), tumor necrosis factor-α, IL-13, altered oxygen tension, and balloon dilatation of coronary arteries [7][8][9][10][11]. The activation and expression of endothelial arginase II can also be induced by a variety of vascular stimulants, including OxLDL, LPS, TNF-α, IFN-γ, 8-bromocGMP, and hypoxia [7,10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Berkowitz et al (6) had shown that both arginase isotypes were expressed in the rat aortic endothelium. Arginase I had been found to be constitutively expressed in endothelial cells (35), whereas arginase II appeared to be inducible in response to cytokines (8). White et al (32) have demonstrated that arginase type I knockdown could enhance NOS activity in adult rat thoracic aortic tissue, and Zhang et al (35) had shown in the porcine coronary artery that arginase type I is responsible for modulating the endothelial-dependent relaxation.…”
Section: Discussionmentioning
confidence: 99%